EFFECT OF FINANCIAL PERFORMANCE ON CORPORATE VALUE - Fitriani Pujarini (Journal of Accounting and Management Innovation, 2020)
This study was conducted to examine the influence of Return on Equity, Debt to Equity Ratio, Current Ratio and Firm Value on companies registered in the food and beverages subsector manufacturing listed on the Indonesia Stock Exchange. The period used in this study is five (5) years, starting from 2013 to 2017.       This study uses secondary data, namely obtaining data in the form of annual financial statements that contain variables Return on Equity Ratio, Debt to Equity Ratio and  Current Ratio on Firm Value in 10 samples of food and beverages sub-sector manufacturing companies listed on the Indonesia Stock Exchange. Processing and data analysis techniques used were accounting analysis, descriptive statistical analysis, multiple linear analysis, classical assumption analysis (normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test), hypothesis testing and coefficient of determination analysis.